NATIONALITY AND NON-DISCRIMINATION OF CORPORATIONS IN THE OECD MODEL CONVENTION - Oliveira, Monica (Nomos: Revista do Programa de Pós-Graduação em Direito da UFC, 2017)
Recently, the tax planning of Multinational Enterprises (MNEs) dominates the international taxation debate and triggered the OECD BEPS Project. The tax base erosion prompted the adoption of unilateral tax measures to target the tax planning strategies adopted by MNEs. By nature, the unilateral tax measures provide a different treatment to foreign corporations and the nondiscrimination provision of the Article 24 of the OECD Model Convention shall be observed. The present paper is aimed to discuss the nondiscrimination provision of the OECD Model Convention regarding corporations.